AC Biosusceptometry Technique to Evaluate the Gastrointestinal Transit of Pellets under Influence of Prandial State - Miranda, Jose Ricardo A. [UNESP]; Cora, Luciana A. [UNESP]; Americo, Madileine F. [UNESP]; Romeiro, Fernando Gomes [UNESP] (John Wiley & Sons Inc, 2010)
Multiparticulate dosage forms have been proposed when distal regions of gastrointestinal tract are desirable as target of drugs. It is known that physiological parameters might interfere with the processes related to the drug delivery and absorption and therefore, it is essential to evaluate the behavior of such delivery systems in vivo. The aim of this study was to propose the AC Biosusceptometry technique as a noninvasive and radiation free device to evaluate the gastrointestinal transit of a magnetic multiparticulate dosage form in healthy volunteers under fasting and fed conditions. Magnetic pellets were prepared by the powder layering method of ferrite on nonpareils sugar beads and coated by using Eudragitg (R). Our data showed that the AC Biosusceptometry technique was able to monitoring the gastrointestinal transit of pellets presenting similar profiles as demonstrated by standard techniques. Food intake has markedly influenced the gastric emptying as well as the colon arrival and the small intestine transit of magnetic pellets. (C) 2009 Wiley-Liss, Inc. and the American Pharmacists Association J Pharm Sci 99:317-324, 2010
Keywords: gastrointestinal transit; gastric emptying; solid dosage form; pellets; coating; prandial state; imaging methods; Biosusceptometry; colonic drug delivery; controlled release